Ultra-low temperature synthesis of Ge-based optical materials and devices on Si using GeH3Cl. Issue 36 (26th August 2022) - Zhang, Aixin; Mircovich, Matthew A.; Ringwala, Dhruve A.; Poweleit, Christian D.; Roldan, Manuel A.; Menéndez, José; Kouvetakis, John
Abstract : CMOS-compatible GeH3 Cl is used to develop GeSn semiconductors and Ge/Si photodiodes. Responsivities of the latter display near ideal 0.95 collection efficiency (green) a performance improvement to devices made by other methods such as Ge4 H10 (black). Abstract : We describe an alternative strategy to the fabrication of Ge–Sn based materials on Si by using chlorogermane (GeH3 Cl) instead of the specialty Ge hydrides (Ge2 H6, Ge3 H8, Ge4 H10 ) currently employed as ultra-low temperature sources of Ge. This simpler and potentially more practical chlorinated derivative is obtained in high yields and in research-grade purity by direct reactions of commercial GeH4 and SnCl4 and exhibits favorable physical and chemical properties that make it an effective source of Ge for a wide range of chemical vapor deposition (CVD) processing conditions. As a proof-of concept, we have employed GeH3 Cl to demonstrate deposition of pure Ge and GeSn hetero-structures on large-area Si wafers, at conditions compatible with current specialty methods for next generation technologies but with higher deposition efficiency, ensuring an optimal use of the Ge feedstock. In the case of pure Ge, GeH3 Cl has enabled growth of thick and uniform Ge layers with flat surfaces and relaxed microstructures at 330–360 °C, exhibiting lower residual doping than obtained by alternate Ge hydride methods. GeH3 Cl allows for in situ doping with the same facility as the Ge hydrides, and this has enabled the design and fabrication of homo-structure pin photodetectors exhibiting low dark current densities and closer to ideal optical collection efficiencies when compared to devices produced by other Ge-on-Si approaches. In the case of GeSn, the high reactivity of GeH3 Cl toward Sn hydrides has enabled the formation of mono-crystalline alloy layers at ultra-low temperatures between 200–300 °C and conditions akin to molecular beam epitaxy (MBE). Combined, these results suggest an intriguing potential for this new CVD process in the device-application space. The deployment of GeH3 Cl as a highly reactive low-temperature Ge-source could not only improve on the current wasteful methods that use GeH4, but also eliminate the need for the higher-cost polygermanes.